A study of the response of unsymmetrical shear wall for-high rise building / Yushaida Muhd Yusof - Muhd Yusof, Yushaida (2006)
A study of the response of unsymmetrical shear wall and its analysis is a topic that is unfamiliar to many engineers. This research is to try something new to the unsymmetrical shear wall with the different orientation. This research is very important in order to avoid any possible matter for high rise building in the future especially when the shear wall just focus to the framing of building. Therefore, by providing data information and analysis, the professional and decision maker can design the unsymmetrical shear wall with better strength besides considering the cost. This research focuses for the response of unsymmetrical shear wall in high rise building and the strength behavior of unsymmetrical shear wall for the building of 45m height. The three new samples have been analyzed by LUSAS software and by analysis; the loading for three new samples was lesser than the original sample plan. The outputs from the software were displacement, shear stress and sway digram of the building. From the comparison between the original sample and three other samples, shows the design of the original sample is better than design of three new samples because the shear wall of the three new samples just focus on the framing of the building.